The Effect of Capital Structure on the Profitability of Manufacturing Companies in Indonesia - Agung, Rina Asmara; Murdiawati, Murdiawati; Guswati, Guswati (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This qualitative literature review aims to examine the effect of capital structure on the profitability of manufacturing companies in Indonesia. Over recent years, the dynamic relationship between capital structure and financial performance has gained significant attention from researchers and practitioners, particularly within the context of emerging economies like Indonesia. Capital structure decisions, including the proportion of debt and equity financing, are critical as they influence not only the cost of capital but also the firm's ability to generate profits. By analyzing various studies and theories related to capital structure, this review identifies key factors such as the impact of debt levels, equity financing, and the trade-off between risk and return in determining profitability. Manufacturing companies, given their capital-intensive nature, often face unique challenges in managing these financial structures. This study specifically focuses on how these companies in Indonesia navigate such challenges in a highly competitive market. Findings from the reviewed literature suggest that a well-balanced capital structure can enhance profitability by optimizing the cost of capital and increasing the firm's operational efficiency. However, an excessive reliance on debt financing tends to elevate financial risks, potentially diminishing profitability. Moreover, industry-specific factors such as market volatility, regulatory environment, and economic conditions are highlighted as critical elements that mediate the relationship between capital structure and profitability. The contribution of this research lies in offering a comprehensive understanding of how capital structure influences the profitability of manufacturing companies in Indonesia, providing valuable insights for managers, investors, and policymakers. The review also outlines the gaps in existing research and proposes future directions for further empirical studies in this domain.